Reinforced microcrystalline glass as well as preparation method and application thereof

CN119731131APending Publication Date: 2025-03-28CHONGQING AUREAVIA HI TECH GLASS CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202380053853.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing crystal-ceramic glass has insufficient anti-fall performance and cannot meet the performance requirements of mid-to-high-end mobile phones.

Method used

By introducing lithium feldspar and lithium disilicate crystal phases into the glass-ceramics and chemically strengthening them, a strengthened glass-ceramics with excellent anti-fall properties is formed, specifically including the formation of a compressive stress layer on the surface and a tensile stress layer inside. To meet specific stress characteristics and oxide composition, ceramic treatment and salt bath chemical strengthening processes are used.

Benefits of technology

Significantly improves the anti-fall performance of glass-ceramics, it can reach an average anti-sandpaper drop height of 1.30 to 1.80m under 80-grit sandpaper conditions, and provides better protection performance in smart terminal products such as mobile phones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731131A_ABST
    Figure CN119731131A_ABST
Patent Text Reader

Abstract

The present invention provides a strengthened glass ceramic and a preparation method and application thereof, the strengthened glass ceramic contains a petalite crystal phase and a lithium disilicate crystal phase, the strengthened glass ceramic has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside, and the strengthened glass ceramic satisfies: (CS50 / DOL0) > = 0.332 * (surface CS / CTCV); dOL0 is greater than or equal to 0.187 t; 1.01% > = delta alpha > = 0.65%, and delta alpha = 5 * 10 <-5 > * CTAV + 0.0026. Under the condition of 80-mesh abrasive paper, the average height of the reinforced microcrystalline glass in falling failure can reach 1.30-1.80 m. Compared with the prior art, the reinforced microcrystalline glass disclosed by the invention has the advantages that the breaking resistance on rough ground is obviously improved, and the reinforced microcrystalline glass can be used as a protective cover plate material of intelligent terminal products such as mobile phones.
Need to check novelty before this filing date? Find Prior Art

Description

A kind of strengthened microcrystalline glass and its preparation method and application

[0001] Related applications

[0002] This application claims priority to the prior application document with application number CN202210869057.X filed with the State Intellectual Property Office of China on July 22, 2022, and incorporates its entire contents into this document. Technical Field

[0003] The present invention relates to the field of lithium aluminum silicon glass-ceramics, and in particular to a glass-ceramic with excellent drop resistance and a preparation method thereof. Technical Background

[0004] With the advent of the smart phone era, mobile phones have become an indispensable communication tool in daily life. As the number of mobile phone users continues to grow, the rate of mobile phone upgrades and replacements continues to increase to meet user requirements and enhance the user experience. As mobile phones become increasingly lightweight and thinner, the performance requirements for their cover glass are gradually increasing. Among them, microcrystalline glass with petalite and lithium disilicate as the main crystalline phases can achieve a crystallinity exceeding 70wt%, and its transmittance in the 360-740nm wavelength range is close to that of commonly used lithium aluminosilicate glass. Furthermore, it can be chemically strengthened in salt baths to further enhance its mechanical properties such as drop resistance and impact resistance. Therefore, it stands out and has attracted widespread attention in the cover glass industry.

[0005] The reason why cover glass breaks during use is usually that it falls from a height and collides with sharp objects (such as fine sand, cement, and pebbles). The glass surface is partially damaged, and microcracks are formed at the damage point. The cracks extend from the glass surface to the inside. When the cracks extend through the compressive stress layer on the glass surface and reach the tensile stress layer area, the cracks will rapidly expand in the tensile stress area, causing the cracks to penetrate the entire glass, thereby causing the glass to be damaged and broken.

[0006] The existing patented microcrystalline glass with petalite and lithium disilicate as the main crystal phases mainly suppresses crack propagation by increasing CT and DOL_0 after strengthening, thereby improving the glass's anti-destructive performance.

[0007] CN201980020541.1 obtains the absolute value of the maximum surface compressive stress through a specific strengthening method, which is 1.8 to 2.2 times the absolute value of the maximum central tensile stress, and the maximum CT value reaches 140MPa.

[0008] CN202010348413.4 uses two-step salt mixing strengthening to make the maximum CT reach 120MPa, DOL_0≥100μm, and the maximum tensile stress linear density reach 50000MPa / mm.

[0009] Summary of the Invention

[0010] However, the drop resistance of these glasses is still insufficient and it is difficult to meet the performance requirements of current mid-to-high-end mobile phones.

[0011] In response to the problem that the drop resistance of the microcrystalline glass in the existing technology is difficult to meet the demand, the inventors have conducted extensive research and provided a microcrystalline glass with better drop resistance, which has significantly improved drop resistance compared to the existing technology.

[0012] Specifically, the present invention provides the following technical solutions:

[0013] 1. A strengthened glass-ceramic, wherein the strengthened glass-ceramic contains a petalite crystal phase and a lithium disilicate crystal phase, and the strengthened glass-ceramic has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside;

[0014] The strengthened glass-ceramics meets the following requirements:

[0015] DOL_0≥0.187t, where t is the thickness of the strengthened glass-ceramics;

[0016] 1.01%≥Δα≥0.65%, Δα=5×10 -5 ×|CT_AV|+0.0026;

[0017] (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|);

[0018] in:

[0019] Surface CS: surface compressive stress, in MPa;

[0020] CS_50: compressive stress at a depth of 50 μm from the glass surface, in MPa;

[0021] CT_AV: average tensile stress in the tensile stress layer, in MPa;

[0022] CT_CV: maximum tensile stress in the tensile stress layer, in MPa; and

[0023] DOL_0: Depth of compressive stress layer, in μm.

[0024] 2. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:

[0025] SiO2: 65.00~75.00%,

[0026] Al2O3: 5.00~10.00%,

[0027] P2O5: 1.00~5.00%,

[0028] CaO: 0.10~3.00%,

[0029] ZrO2: 1.00~10.00%,

[0030] Na2O: 0~5.00%,

[0031] Li2O: 5.00~15.00%,

[0032] K2O: 0.10~3.00%, and

[0033] B2O3: 0~4.00%.

[0034] 3. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:

[0035] SiO2: 68.00~72.00%,

[0036] Al2O3: 5.00~10.00%,

[0037] P2O5: 1.00~3.00%,

[0038] CaO: 0.10~1.00%,

[0039] ZrO2: 2.00~8.00%,

[0040] Na2O: 0~1.00%,

[0041] Li2O: 8.00~13.00%,

[0042] K2O: 0.10-1.00%, and

[0043] B2O3: 0~2.00%.

[0044] 4. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:

[0045] SiO2: 70.00~72.00%,

[0046] Al2O3: 6.00~8.00%,

[0047] P2O5: 1.50~3.00%,

[0048] CaO: 0.50~1.00%,

[0049] ZrO2: 5.00~7.00%,

[0050] Na2O: 0.05~0.60%,

[0051] Li2O: 9.00~12.00%,

[0052] K2O: 0.10-0.50%, and

[0053] B2O3: 0.10~1.00%.

[0054] 5. The strengthened glass-ceramics according to technical solution 1, wherein the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight:

[0055] SiO2: 70.06~71.65%,

[0056] Al2O3: 7.24~7.43%,

[0057] P2O5: 2.49~2.83%,

[0058] CaO: 0.77~0.98%,

[0059] ZrO2: 5.40~6.11%,

[0060] Na2O: 0.06~0.31%,

[0061] Li2O: 11.10~11.95%,

[0062] K2O: 0.13~0.37% and

[0063] B2O3: 0.21~0.91%.

[0064] 6. The strengthened microcrystalline glass according to any one of technical solutions 1 to 5, wherein the total content of the petalite crystal phase and the lithium disilicate crystal phase in the strengthened microcrystalline glass is greater than 75 wt%.

[0065] 7. The strengthened microcrystalline glass according to any one of technical solutions 1-6, wherein, at a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 80-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is 1.30 to 1.80 m.

[0066] 8. The strengthened microcrystalline glass according to any one of technical solutions 1 to 7, wherein, at a thickness of 0.7 mm, the strengthened microcrystalline glass is transparent and has a transmittance of not less than 90.00% for light of a wavelength of 550 nm.

[0067] 9. The method for preparing the tempered glass-ceramics according to any one of technical solutions 1 to 8, characterized in that it comprises the following steps:

[0068] (1) Preparation of substrate glass: After mixing the glass raw materials, adding a clarifier, melting and forming, and annealing to obtain the substrate glass;

[0069] (2) Preparation of glass-ceramics: performing nucleation and crystallization treatments on the substrate glass obtained in step (1) to obtain glass-ceramics;

[0070] (3) cold working the glass-ceramics obtained in step (2) to obtain a polished sheet; and

[0071] (4) The polished sheet obtained in step (3) is subjected to chemical strengthening treatment to obtain strengthened microcrystalline glass.

[0072] 10. The preparation method according to technical solution 9, wherein, in step (1), the annealing temperature is 450-600°C, optionally 450-550°C, and the annealing time is 6-240 hours, and the optional annealing time is 6-120 hours. Annealing is divided into four stages: heating, heat preservation, slow cooling, and rapid cooling. Theoretically, at a certain temperature, the longer the annealing time, the less residual stress. However, considering the time cost, the time should not be too long. Sample bricks of different specifications require different annealing times to reduce the thermal stress of the sample bricks to a usable range. The larger the sample brick size, the longer the required annealing time.

[0073] 11. The preparation method according to technical solution 9 or 10, wherein, in step (2), when performing nucleation treatment, the nucleation temperature is 500-700°C, optionally 540-570°C, and the nucleation treatment time is optionally 10-1440 min.

[0074] 12. The preparation method according to technical solution 11, wherein, in step (2), when performing nucleation treatment, the temperature is raised to the nucleation temperature at a heating rate of 5 to 20°C / min, and optionally at a heating rate of 10°C / min.

[0075] 13. The preparation method according to any one of technical solutions 9 to 12, wherein, in step (2), during the crystallization treatment, the crystallization temperature is 640-750°C, optionally 660-740°C, or optionally 670-740°C, and the optional crystallization treatment time is 5-1440 min.

[0076] 14. The preparation method according to technical solution 13, wherein, in step (2), when performing crystallization treatment, the temperature is raised to the crystallization temperature at a heating rate of 5 to 20°C / min, and optionally at a heating rate of 10°C / min.

[0077] 15. The preparation method according to any one of technical solutions 9 to 14, wherein, in step (4), the polishing sheet obtained in step (3) is chemically strengthened in a pure sodium salt or lithium sodium potassium mixed salt bath at 380 to 550° C., and the strengthening time can be selected from 1 to 24 hours.

[0078] 16. The preparation method according to technical solution 15, wherein, in step (4), the sodium ions in the salt bath are provided by any one or more of sodium nitrate, sodium sulfate and sodium carbonate, the potassium ions are provided by any one or more of potassium nitrate, potassium sulfate and potassium carbonate, and the lithium ions are provided by one or more of lithium nitrate, lithium sulfate and lithium carbonate.

[0079] 17. The preparation method according to technical solution 15 or 16, wherein the composition of the lithium-sodium-potassium mixed salt bath is: calculated by mass ratio, containing 0.1-100 wt% NaNO3 and 0-99.9 wt% KNO3, and containing 0-10 wt% LiNO3 relative to the total mass of NaNO3 and KNO3.

[0080] 18. The preparation method according to technical solution 15 or 16, wherein the composition of the lithium-sodium-potassium mixed salt bath is: calculated by mass ratio, containing 30-95 wt% NaNO3 and 5-70 wt% KNO3, and containing 0.01-1 wt%, optionally 0.01-0.1 wt% LiNO3 relative to the total mass of NaNO3 and KNO3.

[0081] 19. According to the preparation method described in any one of technical solutions 9-18, the chemical strengthening treatment in step (4) is carried out 1 to 3 times.

[0082] 20. The preparation method according to any one of technical solutions 9 to 19, wherein in step (1), the clarifier is selected from any one or more of NaCl, Sb2O3, As2O3, nitrate, and sulfate, and the mass ratio of the clarifier added to the glass can be 0.10-1.00 wt%, more preferably 0.50-1.00 wt%; and / or

[0083] In the step (1), the melt molding is performed at 1400 to 1650°C.

[0084] 21. The strengthened microcrystalline glass obtained by the preparation method described in any one of technical solutions 9-20.

[0085] 22. Use of the tempered glass-ceramics described in any one of Technical Solutions 1 to 8 or the tempered glass-ceramics described in Technical Solution 21 as a protective cover in a mobile device.

[0086] The stress characteristics of the strengthened glass-ceramics provided by the present invention satisfy 1.01%≥Δα≥0.65% (Δα=5×10 -5 When (CS_50 / DOL_0) ≥ 0.332 × (surface CS / |CT_CV|) and DOL_0 ≥ 0.187t, the average drop resistance on 80-grit sandpaper can reach 1.30 to 1.80 meters. This tempered glass-ceramic exhibits significantly improved drop resistance on rough surfaces compared to existing technologies and can be used as a protective cover material for smart terminal products such as mobile phones. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] FIG1 is a DSC graph of the substrate glass in Example 3 of the present invention, which is heated to 1000° C. at a rate of 10° C. / min in nitrogen;

[0088] FIG2 is a graph showing the transmittance of the glass-ceramics of Example 3 of the present invention at a wavelength of 200 nm to 1000 nm;

[0089] FIG3 is an X-ray diffraction pattern of the glass-ceramics of Example 3 of the present invention;

[0090] FIG4 is a schematic diagram of the tempered glass-ceramics of the present invention when it falls and breaks. DETAILED DESCRIPTION

[0091] In order to solve the problem of insufficient drop resistance of microcrystalline glass in the prior art, the present invention provides a transparent microcrystalline glass with petalite and lithium disilicate as the main crystal phases, which can be chemically strengthened to obtain strengthened microcrystalline glass. The strengthened microcrystalline glass has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside. Since the tensile stress layer has not undergone ion exchange, its composition is the same as that of the transparent microcrystalline glass before strengthening.

[0092] The strengthened glass-ceramic meets the following stress characteristics:

[0093] DOL_0≥0.187t, t is the thickness of glass-ceramics;

[0094] 1.01%≥Δα≥0.65%, Δα=5×10 -5 ×|CT_AV|+0.0026;

[0095] (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|);

[0096] Δα is a function that is positively correlated with the absolute value of the average tensile stress. When Δα in the tempered microcrystalline glass is greater than 1.01%, the tensile stress of the microcrystalline glass product is too large, which may cause the microcrystalline glass to self-explode. When Δα is less than 0.65%, the tensile stress of the microcrystalline glass product is small and the drop resistance is poor.

[0097] (CS_50 / DOL_0) / (surface CS / |CT_CV|) is the comprehensive relationship between surface compressive stress, central tensile stress and stress layer depth. When (CS_50 / DOL_0) is less than 0.332×(surface CS / |CT_CV|), microcracks are likely to form when the glass comes into contact with sharp objects and expand inward, resulting in a decrease in the glass's drop resistance.

[0098] DOL_0 is the depth of the compressive stress layer (abbreviated as "compressive stress layer depth"). When DOL_0 is less than 0.187t, the compressive stress layer is relatively shallow. When the glass comes into contact with sharp objects, the cracks generated can more easily penetrate the compressive stress layer and reach the tensile stress zone, thereby reducing the glass's drop resistance.

[0099] In the present invention, those skilled in the art can select the thickness of the strengthened glass-ceramics according to needs. For example, in some embodiments, the thickness of the strengthened glass-ceramics is 0.2-2.0 mm.

[0100] The composition range of the strengthened glass-ceramics of the present invention is such that the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides, calculated by weight:

[0101] SiO2: 65.00~75.00%,

[0102] Al2O3: 5.00~10.00%,

[0103] P2O5: 1.00~5.00%,

[0104] CaO: 0.10~3.00%,

[0105] ZrO2: 1.00~10.00%,

[0106] Na2O: 0~5.00%,

[0107] Li2O: 5.00~15.00%,

[0108] K2O: 0.10~3.00%,

[0109] B2O3: 0~4.00%.

[0110] Optionally, the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides, calculated by weight:

[0111] SiO2: 68.00~72.00%, optional 70.00~72.00%,

[0112] Al2O3: 5.00~10.00%, optional 6.00~8.00%,

[0113] P2O5: 1.00~3.00%, optional 1.50~3.00%,

[0114] CaO: 0.10~1.00%, optional 0.50~1.00%,

[0115] ZrO2: 2.00~8.00%, 5.00~7.00% optional,

[0116] Na2O: 0~1.00%, optional 0.05~0.60%,

[0117] Li2O: 8.00~13.00%, optional 9.00~12.00%,

[0118] K2O: 0.10~1.00%, optional 0.10~0.50%,

[0119] B2O3: 0~2.00%, optional 0.10~1.00%.

[0120] Further optionally, the tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides, calculated by weight:

[0121] SiO2: 70.06~71.65%,

[0122] Al2O3: 7.24~7.43%,

[0123] P2O5: 2.49~2.83%,

[0124] CaO: 0.77~0.98%,

[0125] ZrO2: 5.40~6.11%,

[0126] Na2O: 0.06~0.31%,

[0127] Li2O: 11.10~11.95%,

[0128] K2O: 0.13~0.37% and

[0129] B2O3: 0.21~0.91%.

[0130] In the strengthened glass-ceramics of the present invention, the total content of the petalite crystal phase and the lithium disilicate crystal phase accounts for more than 75wt% of the strengthened glass-ceramics, and can be optionally greater than or equal to 79wt%, and more preferably greater than or equal to 80wt%. It is also accompanied by possible impurity phases such as quartz, spodumene, and lithium metasilicate. Lithium disilicate Li2Si2O5 is an orthorhombic crystal, which is often flat and has a distinct dissociation surface. Due to its irregular orientation, this crystal phase forces cracks to extend along distorted grain boundaries, reducing the possibility of crack propagation. 10 It is a monoclinic crystal, Li and O are tetrahedral coordinated, petalite can be chemically strengthened in a salt bath, the Na in the salt bath + Substitute part of Li in petalite + .

[0131] In some embodiments, the strengthened glass-ceramics of the present invention comprises a total content of the petalite crystalline phase and the lithium disilicate crystalline phase of 79 wt % to 97 wt %. In some embodiments, the strengthened glass-ceramics of the present invention comprises a total content of the petalite crystalline phase and the lithium disilicate crystalline phase of 79 wt %, 80.00 wt %, 81.00 wt %, 82.00 wt %, 83.00 wt %, 84.00 wt %, 85.00 wt %, 86.00 wt %, 87.00 wt %, 88.00 wt %, 89.00 wt %, 90.00 wt %, 91.00 wt %, 92.00 wt %, 93.00 wt %, 94.00 wt %, 95.00 wt %, 96.00 wt %, or 97.00 wt %, or any ratio within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as needed, as long as the glass with the desired properties of the present invention can be obtained.

[0132] In some embodiments, in the strengthened glass-ceramics, the average size of the grains is 10 nm to 50 nm, optionally 10 nm to 30 nm, and more optionally 10 nm to 20 nm. In some embodiments, the average size of the grains can be 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 35 nm, 38 nm, 40 nm, 45 nm, 48 nm, or 50 nm, or any ratio within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as needed, as long as the glass-ceramics of the present invention can be obtained.

[0133] The strengthened glass-ceramics of the present invention also has the following stress characteristics:

[0134] Surface CS: 200~680MPa;

[0135] CS_50: 100~400MPa;

[0136] CS_100: 20~150MPa;

[0137] |CT_CV|: 50~210MPa;

[0138] |CT_AV|: 55~150MPa;

[0139] CT_LD: 45000~90000MPa / mm.

[0140] Tempered glass-ceramic's drop resistance / fall resistance:

[0141] At a thickness of 0.7 mm, the tempered glass-ceramics provided by the present invention was subjected to a sandpaper drop resistance test using 80-grit sandpaper. The average sandpaper drop resistance height of the tempered glass-ceramics was 1.30 to 1.80 m.

[0142] At a thickness of 0.7 mm, the strengthened microcrystalline glass provided by the present invention was subjected to a sandpaper drop resistance test using 120-grit sandpaper. The average sandpaper drop resistance height of the strengthened microcrystalline glass was greater than 2.00 m.

[0143] At a thickness of 0.7 mm, the strengthened microcrystalline glass provided by the present invention was subjected to a sandpaper drop resistance test using 180-grit sandpaper. The average sandpaper drop resistance height of the strengthened microcrystalline glass was greater than 2.50 m.

[0144] Strengthening the optical properties of glass-ceramics:

[0145] The transmittance of the strengthened glass-ceramics under light with a wavelength of 200 to 1000 nm was tested, as shown in Figure 2. As can be seen from Figure 2, the transmittance of the strengthened glass-ceramics is high and the transparency is good in the visible light wavelength.

[0146] At a thickness of 0.7 mm, the strengthened micro-ceramic glass is transparent to light with a wavelength of 550 nm and has a transmittance of not less than 90.00%.

[0147] The present invention prepares microcrystalline glass with a high crystal content by ceramicizing lithium aluminosilicate glass, and then places the microcrystalline glass in pure sodium salt or lithium sodium potassium mixed salt for chemical strengthening, so that the glass meets the above-mentioned stress characteristic requirements after strengthening, thereby obtaining better anti-drop performance.

[0148] SiO2, as a forming oxide of the glass network, is an indispensable component of the glass network structure. Properly increasing the SiO2 content can increase the stability and mechanical strength of the glass. However, excessive SiO2 will increase the viscosity of the glass, causing difficulties in melting the glass. Therefore, in the present invention, when the SiO2 content is controlled at 65.00-75.00wt%, it is most effective in increasing the stability and formability of the glass. In some embodiments, the weight percentage of SiO2 is 68.00%-72.00%. In some embodiments, the weight percentage of SiO2 is 70.00%-72.00%. In some embodiments, the weight percentage of SiO2 is 70.06%-71.65%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics may contain 65.00-71.00%, 66.00-71.00%, 67.00-71.00%, 68.00-71.00%, 68.00-69.50%, 67.00-69.50%, 68.00-71.00%, 67.30-71.00%, 67.50-71.00%, 67.70-71.00%. 1.00%, 68.20% to 71.00%, 68.50% to 71.00%, 68.80% to 71.00%, 69.00% to 71.00%, 69.00% to 69.80%, 69.00% to 69.50%, 69.00% to 69.30%, 69.50 to 70.00%, 70.00 to 70.50%, 71.00 to 71.50% or 71.50 to 72.00% SiO2. In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 65.00%, 66.00%, 67.00%, 67.10%, 67.20%, 67.30%, 67.40%, 67.50%, 67.60%, 67.70%, 67.80%, 67.90%, 68.00%, 68.10%, 68.20%, 68.30%, 68.40%, 68.50%, 68.60%, 68.70%, 68.80%, 68.90%, 69.00%, 69.10%, 69.20%, 69.30%, 69.40%, 69.50%, 69.60%, 69.70%, 69.80%, 69.90%, 71.00%, 72.00%, 73.00%, 74.00% or 75.00% SiO2, or SiO2 within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass of the present invention is obtained.

[0149] Al2O3 is an intermediate oxide in glass formation, which can improve the chemical stability of glass. Furthermore, since [Al2O3] is larger than [SiO4], it provides more space for ion exchange, thus promoting ion exchange. However, excessive Al2O3 tends to increase the viscosity of the glass, and the presence of alkaline earth metals can also increase the tendency of glass to crystallize. Therefore, in the present invention, the Al2O3 content is controlled to be between 5.00 and 10.00 wt%. In some embodiments, the weight percentage of Al2O3 can be between 6.00 and 8.00%. In some embodiments, the weight percentage of Al2O3 can be between 7.24 and 7.43%. In some embodiments, the tensile stress layer of the strengthened microcrystalline glass may contain 5.00%, 5.30%, 5.50%, 5.80%, 6.00%, 6.30%, 6.50%, 6.80%, 7.00%, 7.30%, 7.50%, 7.80%, 8.00%, 8.30%, 8.50%, 8.80%, 9.00%, 9.30%, 9.50%, 9.80% or 10.00% Al2O3 by weight, or Al2O3 within a numerical range consisting of any two of the above specific numerical values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass of the present invention can be obtained.

[0150] P2O5 can serve as a glass network forming oxide, promoting the phase separation of the glass, thereby affecting the crystallization of the glass. In the transparent microcrystalline glass of the Li2O-Al2O3-SiO2 system of the present invention, the P2O5 content is controlled at 1.00-5.00 wt%. In some embodiments, the weight percentage of P2O5 can be 1.00% to 3.00%; in some embodiments, the weight percentage of P2O5 can be 1.50% to 3.00%; in some embodiments, the weight percentage of P2O5 can be 2.49% to 2.83%; in some embodiments, the tensile stress layer of the strengthened microcrystalline glass can include 1.00%, 1.20%, 1.50%, 1.70%, 1.80%, 2.00%, 2.20%, 2.50%, 2.80%, 3.00%, 3.20%, 3.50%, 3.80%, 4.00%, 4.20%, 4.50%, 4.80% or 5.00% P2O5 by weight, or P2O5 within a numerical range consisting of any two of the above specific numerical values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics of the present invention can be obtained.

[0151] ZrO2 is an intermediate oxide in glass formation, improving the chemical stability of glass, increasing its hardness and resistance to scratches and drops. Furthermore, due to its high cationic charge and strong electric field, ZrO2 has a significant agglomeration effect on the glass structure and is commonly used as a nucleating agent in glass-ceramics. However, excessive ZrO2 can significantly increase the viscosity of the glass, affecting its formability. Therefore, the ZrO2 content in the transparent glass-ceramics of the Li2O-Al2O3-SiO2 system of the present invention is controlled to be between 1.00 and 10.00 wt%. In some embodiments, the weight percentage of ZrO2 can be 2.00% to 8.00%; in some embodiments, the weight percentage of ZrO2 can be 5.00% to 7.00%; in some embodiments, the weight percentage of ZrO2 can be 5.40% to 6.11%; in some embodiments, the tensile stress layer of the strengthened microcrystalline glass can include 1.00%, 1.20%, 1.40%, 1.60%, 1.80%, 2.00%, 2.20%, 2.40%, 2.60%, 2.80%, 3.00%, 3.20%, 3.40%, 3.60%, 3.80%, 3. %, 4.00%, 4.20%, 4.40%, 4.60%, 4.80%, 5.00%, 5.20%, 5.40%, 5.60%, 5.80%, 6.00%, 6.20%, 6.40%, 6.60%, 6.80%, 7.00%, 7.20%, 7.40%, 7.60%, 7.80%, 8.00%, 8.20%, 8.40%, 8.60%, 8.80%, 9.00%, 9.20%, 9.40%, 9.6%, 9.8% or 10.0% ZrO2, or ZrO2 within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass of the present invention can be obtained.

[0152] CaO, as a network-forming oxide in glass, helps reduce the viscosity of the glass, inhibits glass crystallization during glass forming, and also improves the low-temperature melting property of the glass. However, excessive CaO can reduce the glass's resistance to devitrification. By adding an appropriate amount of CaO, the viscosity of the glass can be reduced while not affecting the glass's crystallization performance. Therefore, the present application controls the CaO content to be between 0.10 and 3.00 wt%. In some embodiments, the weight percentage of CaO can be between 0.10 and 1.00%. In some embodiments, the weight percentage of CaO can be between 0.50 and 1.00%. In some embodiments, the weight percentage of CaO can be between 0.77 and 0.98%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 0.10%, 0.15%, 0.18%, 0.20%, 0.25%, 0.28%, 0.30%, 0.35%, 0.38%, 0.40%, 0.45%, 0.48%, 0.50%, 0.55%, 0.58%, 0.60%, 0.65%, 0.68% by weight. %, 0.70%, 0.75%, 0.78%, 0.80%, 0.85%, 0.88%, 0.90%, 0.95%, 0.98%, 1.00%, 1.50%, 1.75%, 2.00%, 2.25%, 2.50%, 2.75% or 3.00% CaO, or CaO within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the glass-ceramics of the present invention can be obtained.

[0153] Li2O, Na2O, and K2O, as the external oxides of the glass network, can improve the viscosity of the glass and promote the melting and clarification of the glass liquid. At the same time, Li2O and Na2O can also exchange ions with the molten salt bath. The content of the two is an important factor affecting the stress of the glass. In addition, Li2O is also a lithium disilicate (Li2Si2O5), lithium metasilicate (Li2SiO3) and petalite (LiAlSi4O 10 ) are essential chemical components for the formation of crystalline phases. However, the free oxygen provided by Li2O, Na2O, and K2O can destroy the network structure of the glass and affect the intrinsic strength of the glass. Therefore, the present application requires that the Li2O content be controlled within a range of 5.00-15.00 wt%, the Na2O content within a range of 0-5.00 wt%, and the K2O content within a range of 0.10-3.00 wt%.

[0154] In some embodiments, the Li2O content is controlled between 8.00 and 13.00 wt%; in some embodiments, the Li2O content is controlled between 9.00 and 12.00 wt%; in some embodiments, the Li2O content is controlled between 11.10 and 11.95 wt%.

[0155] In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 5.00%, 5.50%, 6.00%, 6.50%, 7.00%, 7.50%, 8.00%, 8.10%, 8.15%, 8.20%, 8.25%, 8.30%, 8.35%, 8.40%, 8.45%, 8.50%, 8.55%, 8.60%, 8.65%, 8.70%, 8.75%, 8.80%, 8.85%, 8.90%, 8.95%, 8.96%, 8.97%, 8.98%, 8.99%, 8.10%, 8.11%, 8.12%, 8.13%, 8.14%, 8.15%, 8.16%, 8.17%, 8.18%, 8.19%, 8.20%, 8.25%, 8.30%, 8.35%, .00%, 9.10%, 9.15%, 9.20%, 9.25%, 9.30%, 9.35%, 9.40%, 9.45%, 9.50%, 9.55%, 9.60%, 9.65%, 9.70%, 9.75%, 9.80%, 9.85%, 9.90%, 9.95%, 10.00%, 10.10%, 10.15%, 10.20%, 10.25%, 10.30%, 10.35%, 10.40%, 10.45%, 10.50%, 10.55%, 10.60 %, 10.65%, 10.70%, 10.75%, 10.80%, 10.85%, 10.90%, 10.95%, 11.00%, 11.10%, 11.15%, 11.20%, 11.25%, 11.30%, 11.35%, 11.40%, 11.45%, 11.50%, 11.55%, 11.60%, 11.65%, 11.70%, 11.75%, 11.80%, 11.85%, 11.90%, 11.95%, 12.00%, 12. 10%, 12.15%, 12.20%, 12.25%, 12.30%, 12.35%, 12.40%, 12.45%, 12.50%, 12.55%, 12.60%, 12.65%, 12.70%, 12.75%, 12.80%, 12.85%, 12.90%, 12.95%, 13.00%, 13.50%, 14.00%, 14.50% or 15.00% Li2O, or Li2O within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass of the present invention can be obtained.

[0156] In some embodiments, the Na2O content is controlled at 0.01-1.00 wt%; in some embodiments, the Na2O content is controlled at 0.05-0.60 wt%; in some embodiments, the Na2O content is controlled at 0.06-0.31 wt%.

[0157] In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include, by weight, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 2.00%, 3.00%, 4.00% or 5.00% Na2O, or Na2O within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass of the present invention is obtained.

[0158] In some embodiments, the K2O content is controlled within the range of 0.10-1.00 wt %; in some embodiments, the K2O content is controlled within the range of 0.10-0.50 wt %.

[0159] In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30% by weight. , 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56% , 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82% %, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 2.00% or 3.00% K2O, or K2O within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass of the present invention can be obtained.

[0160] B2O3, as a flux in the glass formation process, can reduce the high-temperature viscosity of the glass, accelerate glass clarification, and reduce the glass's crystallization ability. However, excessive B2O3 can reduce the chemical stability and mechanical strength of the glass. Therefore, in the present invention, the B2O3 content is controlled to be between 0 and 4.00 wt%. In some embodiments, the B2O3 content is controlled to be between 0 and 2.00%. In some embodiments, the B2O3 content is controlled to be between 0.10 and 1.00%. In some embodiments, the B2O3 content is controlled to be between 0.21 and 0.91%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics may include 0.10%, 0.15%, 0.18%, 0.20%, 0.25%, 0.28%, 0.30%, 0.35%, 0.38%, 0.40%, 0.45%, 0.48%, 0.50%, 0.55%, 0.58%, 0.60%, 0.65%, 0.68%, 0.70%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 0.99%, 0.91%, 0.97%, 0.98%, 0.99%, 0.99%, 0.91%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 0.99%, 0.99%, 0.99%, 0.99%, 0.99%, 0.99%, 0.99%, 0.99%, 0 0.70%, 0.75%, 0.78%, 0.80%, 0.85%, 0.88%, 0.90%, 0.95%, 0.98%, 1.00%, 1.10%, 1.15%, 1.18%, 1.20%, 1.25%, 1.28%, 1.30%, 1.35%, 1.38%, 1.40%, 1.45%, 1.48%, 1.50%, 1. 55%, 1.58%, 1.60%, 1.65%, 1.68%, 1.70%, 1.75%, 1.78%, 1.80%, 1.85%, 1.88%, 1.90%, 1.95%, 1.98%, 2.00%, 2.10%, 2.15%, 2.18%, 2.20%, 2.25%, 2.28%, 2.30%, 2.35%, 2.38 %, 2.40%, 2.45%, 2.48%, 2.50%, 2.55%, 2.58%, 2.60%, 2.65%, 2.68%, 2.70%, 2.75%, 2.78%, 2.80%, 2.85%, 2.88%, 2.90%, 2.95%, 2.98%, 3.00%, 3.10%, 3.15%, 3.18%, 3.20%, 3.25%, 3.28%, 3.30%, 3.35%, 3.38%, 3.40%, 3.45%, 3.48%, 3.50%, 3.55%, 3.58%, 3.60%, 3.65%, 3.68%, 3.70%, 3.75%, 3.78%, 3.80%, 3.85%, 3.88%, 3.90%, 3.95%, 3.98% or 4.00% B2O3, or B2O3 within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges as long as the microcrystalline glass of the present invention can be obtained.

[0161] Explanation of terms:

[0162] Base glass: glass that has not been subjected to nucleation, crystallization and strengthening treatments.

[0163] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both a glass phase and a crystal phase (also called a microcrystalline phase or a crystalline phase) and is prepared by targeted and controlled crystallization of the base glass.

[0164] Nucleation: Through heat treatment, the nucleating material in the glass grows small crystal nuclei.

[0165] Crystallization: Glass grows a certain type of crystal based on the crystal nucleus through heat treatment.

[0166] Crystalline phase: Crystalline phase is the microscopic structure of crystals, and is a general term for parts composed of a large number of crystalline solid phases.

[0167] CT_LD: tensile stress linear density, the ratio of the sum of the tensile stresses of the tempered glass-ceramic measured by the SLP-2000 stress meter to the glass thickness.

[0168] The glass-ceramics is placed in a salt bath for ion exchange to form a compressive stress layer (i.e., a strengthening layer). During the ion exchange process, a tensile stress layer is formed inside the glass. Specifically, during chemical strengthening, ions with large radii in the salt bath are exchanged with ions with small radii in the glass, thereby forming a compressive stress layer on the surface of the glass and a tensile stress layer inside the glass. Compared to the glass-ceramics before strengthening, the occurrence of ion exchange causes the composition of the compressive stress layer to change. Since the ion exchange depth is usually less than or equal to the thickness of the compressive stress layer, the composition of the tensile stress layer inside the glass does not change, that is, the composition of the tensile stress layer is the same as that of the glass-ceramics before strengthening.

[0169] The tensile stress layer has an upper boundary at a certain distance from the upper surface of the strengthened microcrystalline glass and a lower boundary at a certain distance from the lower surface of the strengthened microcrystalline glass. A curve drawn with the tensile stress at a point on a line segment in the tensile stress layer that is perpendicular to the upper boundary and the lower boundary and whose upper and lower end points fall on the upper boundary and the lower boundary respectively as the Y-axis and the distance from the corresponding point to the upper boundary as the X-axis is recorded as a tensile stress curve. The ratio of the definite integral of the tensile stress curve to the thickness of the strengthened microcrystalline glass is recorded as the tensile stress linear density, which is the ratio of the sum of the tensile stresses of the strengthened microcrystalline glass measured by the SLP-2000 stress meter to the glass thickness.

[0170] |CT_AV|: Absolute value of average tensile stress, specifically the absolute value of the average value of all tensile stresses in the tensile stress layer, obtained by testing with the SLP-2000 stress meter.

[0171] DOL_0: Depth of the compressive stress layer, also known as the depth of the compressive stress layer, refers to the distance from any surface of the micro-glass to the position close to the surface where the compressive stress is zero, obtained by testing with the SLP-2000 stress meter.

[0172] |CT_CV|: Maximum central tensile stress or absolute value of maximum tensile stress, specifically the absolute value of the maximum value of all tensile stresses in the tensile stress layer, obtained by testing with the SLP-2000 stress meter.

[0173] Surface compressive stress: Surface CS. After chemical strengthening of glass-ceramics or glass-ceramics, smaller alkali metal ions on the surface are replaced by larger alkali metal ions. Due to the "crowding" effect of these larger alkali metal ions, compressive stress is generated on the glass surface, known as surface compressive stress. Surface CS is measured using an SLP-2000 stress meter.

[0174] CS_50: compressive stress at a depth of 50 μm from the glass surface.

[0175] CS_100: compressive stress at a depth of 100 μm from the glass surface.

[0176] Transmittance: The ratio of the radiant energy that is projected and passes through the object to the total radiant energy that is projected onto the object in the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.

[0177] Refractive index: The ratio of the speed of light in a vacuum to the speed of light in the medium.

[0178] In the embodiments and comparative examples of the present invention, the transmittance of the glass-ceramics at a wavelength of 550 nm is the average transmittance of multiple glass samples from the same batch measured at a wavelength of 550 nm. At least 5 samples from each batch of glass-ceramics are tested.

[0179] SOC: Photoelastic coefficient. Photoelasticity refers to the anisotropic birefringence of transparent materials when subjected to stress. By measuring the photoelastic coefficient and birefringence, the residual stress (MPa) within the material can be determined.

[0180] Instruments and test methods

[0181] Glass thickness: Determined by micrometer testing. The change in thickness of glass-ceramics before and after chemical strengthening is very small and can be ignored.

[0182] Crystal content test: The glass-ceramic sample is tested using an X-ray diffractometer to obtain an XRD diffraction peak curve. The test result file (RAW format) of the X-ray diffractometer (Shimadzu XRD-6000) is then imported into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud) for fitting and calculation. The crystal content in the glass-ceramic sample can be obtained. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6000. The diffraction angle range used in the test is 2θ = 10 to 50°, the scanning speed is 6° / min, the operating voltage is 40kV, and the operating current is 30mA.

[0183] The average size of the grains (or also called the average grain size) is obtained by testing the glass-ceramic sample using an X-ray diffractometer, and using the Scherrer formula D = Kλ / (βcosθ) for the result data obtained from the XRD test, where λ is the X-ray wavelength, β is the peak half-height width, and K = 0.89, to obtain the average size of the grains.

[0184] Transmittance testing: Glass-ceramic transmittance was measured using professional testing instruments, referring to the GB / T 7962.12-2010 Test Methods for Colorless Optical Glass - Part 12: Spectral Transmittance standard. The instruments used in this article were a Konica Minolta CM-3600A spectrophotometer and a Shimadzu UV-Vis spectrophotometer.

[0185] Surface compressive stress (surface CS), CS_50, CS_100, CT_AV, CT_CV, and DOL_0 were tested using a Luceo (Japan) SLP-2000 stress meter with a light source wavelength of 518 nm, SOC = 25.5 (nm / cm) / MPa, refractive index = 1.54, and exposure time: 300 μsec.

[0186] When testing surfaces with CS, CS_50, CS_100, CT_AV, CT_CV, and DOL_0, apply a drop of the specified refractive fluid to the strain gauge. Clean the tempered glass-ceramic and place it on the test path to measure the value. The refractive index of the refractive fluid used with the SLP-2000 is 1.51.

[0187] CT_LD is related to the thickness, strengthening depth and average tensile stress of the glass sheet and can be used to evaluate the drop resistance of the glass sheet. In the present invention, the CT_LD satisfies the following formula:

[0188] Where d represents the thickness of the glass-ceramic sheet (the glass thickness in the following examples and comparative examples of the present invention is 0.7 mm), in mm; DOL_0 represents the depth of the compressive stress layer, in μm; and CT_AV represents the internal average tensile stress, which is calculated as its absolute value, in MPa. In the present invention, the calculation formula for tensile stress linear density is calculated by substituting the data according to the above units, and the calculated result is obtained. The units are not involved in the calculation.

[0189] Differential Scanning Calorimetry (DSC) testing: The sample was ground and passed through a 200-mesh sieve. The test conditions were room temperature to 1000°C, with a heating rate of 10°C / min. The testing instrument was a Mettler-Toledo TGA / DSC3+ thermogravimetric and simultaneous thermal analyzer. The results are shown in Figure 1.

[0190] Average sandpaper drop resistance: The value obtained by dividing the sum of the sandpaper drop resistance heights measured for multiple glass samples by the number of samples measured. It is used to indicate the glass's resistance to contact surface cracking.

[0191] Take at least 10 samples from each batch for testing, and the average resistance to sandpaper drop height

[0192] Where n is the number of glass samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample tested.

[0193] Among them, the test method for a single sample's resistance to sandpaper drop height is:

[0194] Step 1: Place the glass sample to be tested, which is 158.8mm x 72.8mm x 0.7mm in length, width and thickness, on the front of a 200g model machine.

[0195] Step 2: Place the model phone on a Green Figure LT-SKDL-CD drop machine with the glass sample facing the sandpaper. Drop the glass sample from a certain drop height onto the 80-mesh, 120-mesh, or 180-mesh sandpaper directly below the model phone to simulate a normal mobile phone drop.

[0196] If the glass sample does not break, the drop height of the model machine is increased in a certain pattern. For example, the drop height starts from 0.4m and the sample is dropped once. If it does not break, the drop height is increased by 0.1m each time until the glass sample breaks.

[0197] Step 3: Record the last drop height of the glass sample when it breaks as the sandpaper drop height. For example, if the drop height when it breaks is 0.5m, the sandpaper drop height of the sample is 0.4m.

[0198] The method for preparing the tempered glass-ceramics of the present invention comprises the following steps:

[0199] (1) Preparation of substrate glass:

[0200] Mix the ingredients according to the formula for 30 minutes, add a clarifier after mixing, and melt in a platinum crucible at 1400-1650°C for 5 hours. Then pour it into a molding mold for molding. After cooling to 900°C, put it into an annealing furnace at 450-600°C, optionally 450-550°C, and anneal for 6-240 hours, optionally annealing for 6-120 hours. Then cool it to room temperature with the furnace to obtain the base glass.

[0201] The clarifier can be any one or more substances selected from NaCl, Sb2O3, As2O3, nitrate, sulfate, etc., and the mass ratio of the clarifier added to the base glass raw material is 0.10-1.00wt%, that is, the amount of the clarifier accounts for 0.10-1.00wt% of the total amount of the base glass raw material.

[0202] (2) Preparation of glass-ceramics:

[0203] Transparent micro-ceramic glass bricks can be prepared by subjecting the substrate glass to the following nucleation treatment and crystallization treatment in sequence.

[0204] During the nucleation treatment, the temperature is raised to the nucleation temperature at a rate of 5 to 20°C / min, optionally 10°C / min, with the nucleation temperature being 500 to 700°C, and the nucleation treatment time being 10 to 1440 minutes. During the crystallization treatment, the temperature is raised to the crystallization temperature at a rate of 5 to 20°C / min, optionally 10°C / min, with the crystallization temperature being 640 to 750°C, and the crystallization treatment time being 5 to 1440 minutes. The nucleation treatment time here refers to the time the crystallization furnace is kept at the set nucleation temperature after being heated at the set heating rate. The crystallization treatment time here refers to the time the crystallization furnace is kept at the set crystallization temperature after being heated at the set heating rate.

[0205] (3) Sample cold processing:

[0206] The microcrystalline glass bricks obtained in step (2) are subjected to cold working treatment, wherein the cold working treatment includes slicing treatment. Before slicing treatment, the microcrystalline glass bricks can be shaped, and after slicing treatment, they can be subjected to CNC treatment, grinding treatment, and polishing treatment in sequence, or after slicing treatment, at least one of CNC treatment, grinding treatment, and polishing treatment is selected to perform glass piece modification treatment to obtain microcrystalline glass samples of desired size, such as polished pieces with length, width, and thickness of 50mm×50mm×0.7mm, 158.8mm×72.8mm×0.7mm, etc.

[0207] (4) Chemical strengthening:

[0208] The above-obtained microcrystalline glass sample (e.g., polished sheet) is chemically strengthened in a pure sodium salt or lithium sodium potassium mixed salt bath at 380-550°C for 1-24 hours. The sodium ions in the salt bath are provided by any one or more of sodium nitrate, sodium sulfate, and sodium carbonate, the potassium ions are provided by any one of potassium nitrate, potassium sulfate, and potassium carbonate, and the lithium ions are provided by one or more of lithium nitrate, lithium sulfate, and lithium carbonate. The present invention can optionally use a mixed salt composed of lithium nitrate, sodium nitrate, and potassium nitrate for chemical strengthening treatment.

[0209] In some embodiments, the strengthening salt bath of the present invention comprises 0.1-100 wt % NaNO 3 and 0-99.9 wt % KNO 3 , and LiNO 3 is added in an amount of 0-10 wt % relative to the total weight of the salt bath.

[0210] The strengthened microcrystalline glass and the preparation method of the present invention are described in detail below through specific examples.

[0211] Example

[0212] Taking Example 3 as an example, the specific preparation process is as follows:

[0213] According to the composition ratio of substrate glass E shown in Table 1, the total amount of various raw material powders is weighed to 1000 g, and then 5 g of clarifier (NaCl) is added, mixed with a mixer for 30 minutes, and melted in a platinum crucible at 1650°C for 5 hours, then poured into a molding mold for molding, cooled to 900°C, and placed in a 480°C annealing furnace for annealing for 12 hours. After that, it is cooled to room temperature with the furnace (cooled to room temperature at a rate of about 5°C / min) to obtain a substrate glass sample brick; the preparation method of the substrate glass in other embodiments is the same as that in Example 3, wherein the formula ingredient ratios of the substrate glass in Examples 1-6 and Comparative Examples 1-7 correspond to the ingredient letters in Table 1, respectively, and are specifically described in Table 2-2 and Table 2-1.

[0214] The substrate glass was placed in an annealing furnace for nucleation and crystallization treatment. The whole heating rate was set at 10℃ / min, and the temperature was raised from room temperature to 545℃, and kept at 545℃ for 4 hours for nucleation treatment; then the temperature was raised to 675℃, and kept at 675℃ for 90 minutes for crystallization treatment; then the temperature was cooled to room temperature with the furnace to obtain a microcrystalline glass brick.

[0215] After shaping, slicing, CNC, flat grinding and polishing, the glass-ceramic sample bricks are obtained to obtain glass-ceramic samples of desired sizes, such as polished sheets with length, width and thickness of 50mm×50mm×0.7mm, 158.8mm×72.8mm×0.7mm, etc.

[0216] According to the salt bath ratio shown in Table 2-2, 700g of NaNO3, 300g of KNO3, and 0.3g of LiNO3 (70wt% NaNO3 + 30wt% KNO3 + 0.03wt% LiNO3, where 0.03wt% LiNO3 refers to the mass ratio of the additional LiNO3 relative to the total amount of the mixed salt composed of NaNO3 and KNO3) were weighed and placed in a crucible. The mixture was then melted into a liquid state in a strengthening furnace at a temperature of 480°C. The resulting polished wafer was placed in a molten salt bath and strengthened at 480°C for 7 hours to obtain a strengthened microcrystalline glass wafer.

[0217] The obtained strengthened glass-ceramics sheet was subjected to performance testing. After stress testing using SLP-2000, a whole-machine drop test using sandpaper of different mesh sizes was performed. The results are shown in Table 2-2.

[0218] Tables 2-1 and 2-2 show the specific conditions for strengthening the glasses of Comparative Examples 1-7 and Examples 1-6, respectively, including the salt bath mass ratio, salt bath temperature, and salt bath time (comparative example 1 underwent a second strengthening treatment (the strengthening salt baths used for the first and second strengthening treatments are referred to as "one-strength salt bath" and "two-strength salt bath," respectively), while the other examples and comparative examples only underwent a single strengthening treatment). After the different strengthening treatments were performed on the obtained different strengthened glass microcrystal samples, various stress tests and drop tests were performed. The specific stress test data and drop test data are summarized in Tables 2-1 and 2-2, respectively.

[0219] It can be seen from comparative examples 1 to 7 in Table 2-1 that when the microcrystalline glass cannot simultaneously meet 1.01% ≥ Δα ≥ 0.65%, (CS_50 / DOL_0) ≥ 0.332×(surface CS / |CT_CV|), and DOL_0 ≥ 0.187t after strengthening, the average sandpaper drop height of the strengthened microcrystalline glass in the 80-grit sandpaper whole machine drop test is only between 0.88 and 1.15m.

[0220] It can be seen from Examples 1 to 6 in Table 2-2 that the surface CS of the tempered microcrystalline glass of the present invention is greater than 270 MPa, and is within the range of 272-428 MPa; CS_50 is greater than 164 MPa, and is within the range of 164.44-245.83 MPa; CS_100 is greater than 59.55 MPa, and is within the range of 59.55-91.81 MPa; |CT_CV| is greater than 113 MPa, and |CT_CV| is specifically within the range of 113.54-145.86 MPa; |CT_AV| is greater than 85 MPa, and is within the range of 85.49-101.19 MPa; DOL_0 is greater than 130 μm, and is within the range of 130.60-151.57 μm; CT_LD is greater than 50000 MPa / mm, and is within the range of 50477.18-60721.55 MPa / mm. The tempered glass-ceramics of the present invention meet the following characteristics: 1.01% ≥ Δα ≥ 0.65%, (CS_50 / DOL_0) ≥ 0.332 × (surface CS / |CT_CV|), and DOL_0 ≥ 0.187t. In a drop test on 80-grit sandpaper, the tempered glass-ceramics achieved an average drop resistance of over 1.31 meters. Tables 2-1 and 2-2 show that for the same glass sample, the higher the grit of the sandpaper, the greater the average drop resistance. A higher grit sandpaper is associated with smaller coated corundum particles, resulting in a shallower puncture depth.

[0221] In addition, Figure 1 of the present invention is a DSC graph of the base glass in Example 3 of the present invention (glass E composition), which is heated to 1000°C at a heating rate of 10°C / min in nitrogen. It can be seen from the figure that the nucleation temperature of the base glass of this formula is between 530 and 550°C, and the crystallization temperature is between 670 and 700°C.

[0222] Figure 2 is a transmittance curve of the microcrystalline glass of Example 3 (glass E composition) at 200nm to 1000nm tested using Shimadzu UV-visible spectrophotometer UV-2600. It can be seen from the figure that: in the visible light wavelength, the microcrystalline glass of the present invention has a high transmittance and good transparency.

[0223] FIG3 is the X-ray diffraction pattern of the glass-ceramics of Example 3 of the present invention (glass E composition). From the diffraction pattern, it can be seen that Example 3 obtains: the glass-ceramics of the present invention mainly contains petalite and lithium disilicate crystal phases.

[0224] Table 1: Glass-ceramic formula, heat treatment, crystal phase composition and transmittance

[0225] Table 2-1

[0226] Note: In the table, “ / ” means not present or not determined.

[0227] Table 2-2

[0228] Note: Since the upper limit of the drop test machine used for drop test is 2.5m, if the glass still does not break after the drop test at the upper limit test height, it is judged that the average sandpaper drop height of the glass is greater than 2.5m. In the table, " / " means that it does not exist or has not been measured.

Claims

1. A strengthened glass-ceramic comprising a petalite crystal phase and a lithium disilicate crystal phase, wherein the strengthened glass-ceramic has a compressive stress layer formed by chemical strengthening on the surface and a tensile stress layer inside; Its characteristics are: The strengthened glass-ceramics meets the following requirements: DOL_0≥0.187t, where t is the thickness of the strengthened glass-ceramics; 1.01%≥Δα≥0.65%,Δα=5×10 -5 ×|CT_AV|+0.0026; (CS_50 / DOL_0)≥0.332×(surface CS / |CT_CV|); in: Surface CS: surface compressive stress, in MPa; CS_50: compressive stress at a depth of 50 μm from the glass surface, in MPa; CT_AV: average tensile stress in the tensile stress layer, in MPa; CT_CV: maximum tensile stress in the tensile stress layer, in MPa; and DOL_0: Depth of compressive stress layer, in μm.

2. The tempered glass-ceramics according to claim 1, wherein: The tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight: SiO2: 65.00~75.00%, Al2O3: 5.00~10.00%, P2O5: 1.00~5.00%, CaO: 0.10~3.00%, ZrO2: 1.00~10.00%, Na2O: 0~5.00%, Li2O: 5.00~15.00%, K2O: 0.10~3.00%, and B2O3: 0~4.00%.

3. The tempered glass-ceramics according to claim 1, wherein: The tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight: SiO2: 68.00~72.00%, Al2O3: 5.00~10.00%, P2O5: 1.00~3.00%, CaO: 0.10~1.00%, ZrO2: 2.00~8.00%, Na2O: 0~1.00%, Li2O: 8.00~13.00%, K2O: 0.10-1.00%, and B2O3: 0~2.00%.

4. The tempered glass-ceramics according to claim 1, wherein: The tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight: SiO2: 70.00~72.00%, Al2O3: 6.00~8.00%, P2O5: 1.50~3.00%, CaO: 0.50~1.00%, ZrO2: 5.00~7.00%, Na2O: 0.05~0.60%, Li2O: 9.00~12.00%, K2O: 0.10-0.50%, and B2O3: 0.10~1.00%.

5. The strengthened glass-ceramics according to claim 1, wherein: The tensile stress layer of the strengthened glass-ceramics contains the following percentages of oxides by weight: SiO2: 70.06~71.65%, Al2O3: 7.24~7.43%, P2O5: 2.49~2.83%, CaO: 0.77~0.98%, ZrO2: 5.40~6.11%, Na2O: 0.06~0.31%, Li2O: 11.10~11.95%, K2O: 0.13~0.37% and B2O3: 0.21~0.91%.

6. The strengthened glass-ceramics according to any one of claims 1 to 5, wherein: In the strengthened glass-ceramics, the total content of the petalite crystal phase and the lithium disilicate crystal phase is greater than 75 wt %.

7. The strengthened glass-ceramics according to any one of claims 1 to 6, wherein: At a thickness of 0.7 mm, the strengthened glass-ceramics was subjected to a sandpaper drop resistance test using 80-grit sandpaper. The average sandpaper drop resistance height of the strengthened glass-ceramics was 1.30 to 1.80 m.

8. The strengthened glass-ceramics according to any one of claims 1 to 7, wherein: At a thickness of 0.7 mm, the strengthened micro-ceramic glass is transparent to light with a wavelength of 550 nm and has a transmittance of not less than 90.00%.

9. The method for preparing the strengthened glass-ceramics according to any one of claims 1 to 8, characterized in that: Including the following steps: (1) Preparation of substrate glass: After mixing the glass raw materials, adding a clarifier, melting and forming, and annealing to obtain the substrate glass; (2) Preparation of glass-ceramics: performing nucleation and crystallization treatments on the substrate glass obtained in step (1) to obtain glass-ceramics; (3) cold working the glass-ceramics obtained in step (2) to obtain a polished sheet; and (4) The polished sheet obtained in step (3) is subjected to chemical strengthening treatment to obtain strengthened microcrystalline glass.

10. The preparation method according to claim 9, wherein In step (1), the annealing temperature is 450-600° C., optionally 450-550° C., and the annealing time is 6-240 hours, optionally 6-120 hours.

11. The preparation method according to claim 9 or 10, wherein In step (2), when the nucleation treatment is performed, the nucleation temperature is 500-700°C, optionally 540-570°C, and the nucleation treatment time is optionally 10-1440 minutes.

12. The preparation method according to claim 11, wherein In step (2), when performing the nucleation treatment, the temperature is raised to the nucleation temperature at a heating rate of 5 to 20°C / min, and optionally at a heating rate of 10°C / min.

13. The preparation method according to any one of claims 9 to 12, wherein: In step (2), when the crystallization treatment is performed, the crystallization temperature is 640 to 750° C., optionally 660 to 740° C., or optionally 670 to 740° C., and the crystallization treatment time is optionally 5 to 1440 min.

14. The preparation method according to claim 13, wherein In step (2), when performing the crystallization treatment, the temperature is raised to the crystallization temperature at a heating rate of 5 to 20°C / min, and optionally at a heating rate of 10°C / min.

15. The preparation method according to any one of claims 9 to 14, wherein: In step (4), the polishing sheet obtained in step (3) is chemically strengthened in a pure sodium salt or lithium sodium potassium mixed salt bath at 380-550° C., and the strengthening time can be selected from 1 to 24 hours.

16. The preparation method according to claim 15, wherein In step (4), the sodium ions in the salt bath are provided by any one or more of sodium nitrate, sodium sulfate and sodium carbonate, the potassium ions are provided by any one or more of potassium nitrate, potassium sulfate and potassium carbonate, and the lithium ions are provided by one or more of lithium nitrate, lithium sulfate and lithium carbonate.

17. The preparation method according to claim 15 or 16, wherein The composition of the lithium-sodium-potassium mixed salt bath is as follows: calculated by mass ratio, it contains 0.1-100 wt% NaNO3 and 0-99.9 wt% KNO3, and contains 0-10 wt% LiNO3 relative to the total mass of NaNO3 and KNO3.

18. The preparation method according to claim 15 or 16, wherein The composition of the lithium-sodium-potassium mixed salt bath is as follows: calculated by mass ratio, it contains 30-95wt% NaNO3 and 5-70wt% KNO3, and relative to the total mass of NaNO3 and KNO3, it contains 0.01-1wt%, optionally 0.01-0.1wt% LiNO3.

19. The preparation method according to any one of claims 9 to 18, wherein the chemical strengthening treatment in step (4) is performed 1 to 3 times.

20. The preparation method according to any one of claims 9 to 19, wherein in step (1), the clarifier is selected from any one or more of NaCl, Sb2O3, As2O3, nitrates, and sulfates, and the mass percentage of the clarifier added to the glass can be 0.10-1.00 wt%, more preferably 0.50-1.00 wt%; and / or In the step (1), the melt molding is performed at 1400 to 1650°C.

21. The strengthened microcrystalline glass obtained by the preparation method according to any one of claims 9 to 20.

22. Use of the tempered glass-ceramic according to any one of claims 1 to 8 or the tempered glass-ceramic according to claim 21 as a protective cover in a mobile device.

Citation Information

Cited By

  • Glass ceramic ingot and preparation method thereof, glass ceramic, cover plate glass and electronic equipment

    CN122059612A

  • Weather-resistant microcrystalline glass, preparation method thereof, glass device, cover plate glass and electronic equipment

    CN122145042A